Development and Implementation of a Web-Based Journal Management System to Enhance Accreditation and Quality Evaluation - Kamid Kamid; Mukhlash Abrar; Dwi Agus Kurniawan; Eko Nuriyatman (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the Study: This study aims to explore the role and importance of a dedicated journal management website in facilitating the organization, monitoring, and evaluation of journal development at Jambi University. The focus is on how this digital platform can improve journal accreditation processes and overall management efficiency. Methodology: The research adopts a qualitative approach, utilizing focused interviews with 20 respondents from the journal management team at Jambi University. A purposive sampling method was employed to ensure that participants had relevant experience in journal management. Data were collected through in-depth interviews and analyzed to identify common themes related to the challenges and benefits of using a centralized journal management platform. Main Findings: The findings reveal that the implementation of a dedicated journal management website is crucial in supporting the accreditation and development process. Respondents highlighted that such a platform simplifies tracking journal progress, facilitates communication and collaboration among team members, and provides an organized structure for managing evaluation and feedback. The website also enables the team to systematically monitor the quality of journals, helping them meet national and international accreditation standards more efficiently. Novelty/Originality of the Study: This study introduces an innovative approach to managing academic journals through a specialized digital platform, addressing a critical gap in traditional journal management practices. The proposed website not only enhances administrative efficiency but also serves as a strategic tool for continuous quality improvement and collaborative evaluation, ultimately raising the university’s research profile on a broader scale.